Tantangan Bagaimana dalam Mengedukasi Orang Tua terhadap Prespektif Sunat Perempuan pada Bayi Baru Lahir (Tradisi) (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Female Genital Mutilation (FGM) remains a cultural practice among several communities in Indonesia despite global health warnings and international commitments to abolish harmful traditional practices. This article investigates three major aspects: (1) parental knowledge and perception regarding FGM, (2) challenges educators face when providing awareness to parents, and (3) effective strategies within the framework of nonformal education especially PAUD to reduce FGM practice in early childhood. This study uses a systematic literature review approach, integrating national scholarly works particularly journals from Universitas Negeri Padang international research evidence (WHO, UNICEF, BMJ Global Health), and socio-cultural analysis. Findings reveal that parents generally have low health literacy regarding the dangers of FGM and deeply rely on cultural and religious interpretations inherited across generations. The continuity of FGM is influenced by social pressure, traditional authority, and limited trust in formal information. Within the nonformal education domain, PAUD serves as a strategic institution to build dialogue, involve community leaders, and enhance parental awareness through community-based education. This study emphasizes that culturally sensitive, dialogic, and collaborative educational strategies are required to address FGM within communities.